1989
DOI: 10.1007/bf00965513
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of excitatory amino acid receptor ligands by acidic oligopeptides

Abstract: A number of L-glutamyl and L-aspartyl dipeptides, glutathione, gamma-D-glutamylglycine and gamma-D-glutamyltaurine, were tested for their efficacy to displace ligands specific for different subtypes of excitatory amino acid receptors from rat brain synaptic membranes. In general, the L enanthiomorphs of gamma-glutamyl peptides were more potent displacers than gamma-D-glutamylglycine and -taurine but the latter were more specific for the quisqualate type of receptors. gamma-L-glutamyl-L-glutamate was the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…It has also been reported to evoke excitatory potentials in rat cortical slices and to regulate the release of other 788 transmitters, although it remains to be determined whether these actions are mediated via a specific "glutathione receptor" or through other systems, such as excitatory amino acid receptors (Shaw et al, 1996;Janáky et al, 1999;Oja et al, 2000 (Ogita et al, 1995;Janá ky et al, 1999), suggesting that glutathione actions may vary between agonist and antagonist on the basis of specific conditions. Glutathione was also shown to block the binding of radiolabeled AMPA and kainate to non-NMDA receptors (Varga et al, 1989). In a study employing computational modeling, the amino acid binding pockets common to family C G-protein-coupled receptors were probed in silico for the potential to accommodate glutathione .…”
Section: A System X C ϫ and Gsh Signalingmentioning
confidence: 99%
“…It has also been reported to evoke excitatory potentials in rat cortical slices and to regulate the release of other 788 transmitters, although it remains to be determined whether these actions are mediated via a specific "glutathione receptor" or through other systems, such as excitatory amino acid receptors (Shaw et al, 1996;Janáky et al, 1999;Oja et al, 2000 (Ogita et al, 1995;Janá ky et al, 1999), suggesting that glutathione actions may vary between agonist and antagonist on the basis of specific conditions. Glutathione was also shown to block the binding of radiolabeled AMPA and kainate to non-NMDA receptors (Varga et al, 1989). In a study employing computational modeling, the amino acid binding pockets common to family C G-protein-coupled receptors were probed in silico for the potential to accommodate glutathione .…”
Section: A System X C ϫ and Gsh Signalingmentioning
confidence: 99%
“…Glutathione has been reported to have a number of varied actions upon excitatory amino acid neurotransmission. Immunostaining has revealed the presence of binding sites located on astrocytes Guo etal., 1992) while other work has revealed the capacity of glutathione to displace glutamate from its binding sites (Ogita etal., 1986;Ogita and Yoneda, 1988) and possibly to exert an effect on excitatory amino acid neurotransmission directly (Varga et al, 1989;Ogita et al, 1995) and via its effect on the redox state of the NMDA receptor (Janiky etal., 1993). The data from the present study suggest that glutathione in both its reduced and oxidized forms has an inhibitory effect on excitatory amino acid neurotransmission in VB; GSH inhibited responses to NMDA, AMPA and physiological stimuli, while GSSG inhibited only responses to NMDA.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Indirectly as a competitive c-glutamyl antagonist at the NMDA receptors on inhibitory GABAergic interneurons. Our earlier studies [8,42] and those of others [43,44] have shown that glutathione acts at both NMDA and non-NMDA receptors. Agonists of these receptors enhance dopamine release in striatal slices which effects are blocked by their respective antagonists [45,46].…”
Section: Potassium-evoked Releasementioning
confidence: 98%
“…GSH release from brain slices upon depolarization has also been shown to occur [5]. On the other hand, glutathione also acts as a neuromodulator at glutamate receptors [6][7][8][9][10][11]. We have found that both GSH and GSSG preferably interact with 2-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) and N-methyl-D-aspartate (NMDA) receptors.…”
mentioning
confidence: 95%
See 1 more Smart Citation